Getting agriculture moving : essentials for development and modernization - Mosher, Arthur Theodore; Agricultural Development Council (New York : Published for the Agricultural Development Council by Praeger, 1966)
This book covers: the elements of agriculture, the essentials for agricultural development, and the accelerators of agricultural development. The first part analyses the nature of the agricultural production process, of the farmer, of the farm and of the farm business. In a simple manner it draws attention to the physical, biological, psychological, economic, sociological, and cultural elements which meet in the business of farming, and their implications for development. The second part is concerned with the processes which are all considered to be essential in agricultural development - marketing, constantly changing agricultural technology, the local availability of farm requirements, production incentives for farmers, and transport facilities. The final section, dealing with processes which can accelerate development although they may not be indispensable, deals with education, credit facilities for production, group action by farmers, the improvement and expansion of agricultural land, and national planning with respect to agricultural development.
lje 26/01/2018
Loans
Keywords: Agriculture and state